XRF analysis applied to the batateira River formation (Araripe Sedimentary Basin, Ceará State, Brazil) - Roveratti, Gabrielle; Bonotto, Daniel Marcos [UNESP] (My University, 2018)
Recent analytical advances mainly concerning to the use of the X-Rays Fluorescence (XRF) technique have improved the data acquisition in sedimentary basins. This method consists of the processes of electrons excitation and energy conversion in the region of the X-Rays photons. It has been widely used in Geosciences to determinate the elements concentration in samples of rocks, minerals, soils, sediments, etc. The installation of one S8 Tiger spectrometer from Bruker Co. happened at LARIN (Ionizing Radiations Laboratory), UNESPetro (Geosciences Center Applied to Petroleum), IGCE-UNESP-Rio Claro (SP), Brazil, with financial support from Petrobras. Two software packages came with the equipment: QuantExpress (for powder analysis) and GeoMaj (for fused beads analysis). In this chapter are reported the results obtained from several essays held with aliquots of a sample of the lithostratigraphic formation known as “Batateira Layers” that occurs in the Araripe Sedimentary Basin, Ceará State, Brazil. The tests were realized with powdered aliquots, considering the oxides often used in geochemical investigations: SiO2, Al2O3, TiO2, Fe2O3, MnO, CaO, MgO, Na2O, K2O and P2O5. The maximum voltage and current were 50 kV and 50 mA, respectively. The following experimental conditions were adopted: analysis method (Fast, Full and Best), aliquot weight (10g, 8g, 6g, 4g and 2g) and boric acid amount (3.5g and 5g). The most striking variation was for SiO2, Al2O3 and MgO among the investigated parameters. It was possible identify that both the readings method and aliquot weight affected the acquired results. Little or none influence was found in the quantity of boric acid used in the pellets preparation as it was obtained a highly significant Pearson correlation coefficient (r = 0.98) among the readings realized with 3.5 g and 5 g.